Multiple Implications in Respiratory System of Patient As A Function of Anesthetic Drugs: Studying the Remedial Strategies - Ojum S (American Journal of Biomedicine and Pharmacy, 2025)
Anesthetic drugs play a critical role in perioperative care but often present significant implications for the respiratory system. These agents can depress ventilation, alter gas exchange, impair airway reflexes, and exacerbate pre-existing pulmonary conditions, thereby increasing the risk of intraoperative and postoperative complications. This study examines the multiple respiratory effects associated with commonly used anesthetic drugs and highlights the physiological mechanisms underlying these responses. It further explores key remedial strategies such as optimized drug selection, advanced respiratory monitoring, ventilatory support techniques, and multidisciplinary management approaches. Findings emphasize that early identification of respiratory risks and the implementation of targeted interventions can greatly enhance patient safety and outcomes. The study concluded that anesthetic drugs can affect the respiratory system in many ways and may cause breathing challenges during surgery. They can slow ventilation, affect oxygen exchange, and weaken airway protection. Knowing how each drug works helps doctors prevent problems early. One of the recommendations made was that respiratory evaluations to identify high-risk patients and tailor anesthetic choices should be conducted accordingly.